A Multi-level Monte Carlo Simulation for Invariant Distribution of Markovian Switching Lévy-Driven SDEs with Super-Linearly Growth Coefficients - Nguyen, Hoang-Viet; Kieu, Trung-Thuy; Luong, Duc-Trong; Ngo, Hoang-Long; Tran, Ngoc Khue (Methodology and computing in applied probability, 2025)
This paper concerns the numerical approximation for the invariant distribution of Markovian switching Lévy-driven stochastic differential equations. By combining the tamed-adaptive Euler-Maruyama scheme with the Multi-level Monte Carlo method, we propose an approximation scheme that can be applied to stochastic differential equations with super-linear growth drift and diffusion coefficients.